Effects of sheep wintering on subsequent production from pasture - Lockhart, David A. S. (University of Edinburgh, 1968)
1) Four winter grazing treatments (control - rested, grazed November and December, grazed January and February, and grazed November to February at ewes per acre) were applied to lambing Field 1965-66 and Anchordales 1966-67. Production in the following grazing season was measured by recording the number of unit grazing days provided by each paddock. Control yielded the most in both years. Winter grazing altered the growth pattern so that early yields were poor but subsequent performance good. Spring nitrogen was applied in 1966 at 1.5 and 3 cwt./acre Nitrochalk. By mid-June the increase in unit grazing days due to the extra 1.5 cwt./acre Nitrochalk was greater than the differences due to winter grazing. During the previous growing season Anchordales was managed under two nitrogen regimes, high and low. The beneficial effect of the high nitrogen was apparent all through the trial. 2) Paddocks were grazed in winter at 0, 4, 7 and 10 sheep per acre for 76 days. In March damage to pasture was proportional to stocking rate. Nitrogen was applied at 3 and 5 cwt./acre 21% Nitrochalk. The subsequent production was measured at three stages, early bite, silage and hay. Winter grazing seriously reduced yield at the early stage, but by the hay stage yield was not correlated with winter stocking rates. The level of nitrogenous fertiliser was the factor controlling yield of hay. 5) A 5 by 5 Latin square was laid out in the winter of 1966-67. The treatments were control-rested, cut lightly, cut and poached lightly, cut heavily and cut and poached heavily. The yield of early grass was highest on rested plots. Treading was supplementary to defoliation in reducing spring yield of grass. Heavily treated plots had particularly low yields. Regrowth was inversely proportional to yield of early grass.
The effects of sheep wintering on subsequent production from pasture
Keywords: Winter grazing; Nitrogen; Stocking rate; Paddock yield; Pasture damage